Rhodospirillum sp. JY3: An innovative tool to mitigate the phytotoxic impact of galaxolide on wheat (Triticum aestivum) and faba bean (Vicia faba) plants - Madnay, Mahmoud M. Y.; Obaid, Wael A.; Selim, Samy; Mohamed Reyad, Ahmed; Alsherif, Emad A.; Korany, Shereen Magdy; Abdel-Mawgoud, Mohamed; AbdElgawad, Hamada (Frontiers in Plant Science, 2022)
To date, several studies have considered the phytotoxic impact of cosmetics and personal care products on crop plants. Nonetheless, data are scarce about the toxic impact of galaxolide [hexahydro-hexamethyl cyclopentabenzopyran (HHCB)] on the growth, physiology, and biochemistry of plants from different functional groups. To this end, the impact of HHCB on biomass, photosynthetic efficiency, antioxidant production, and detoxification metabolism of grass (wheat) and legume (faba bean) plants has been investigated. On the other hand, plant growth-promoting bacteria (PGPB) can be effectively applied to reduce HHCB phytotoxicity. HHCB significantly reduced the biomass accumulation and the photosynthetic machinery of both crops, but to more extent for wheat. This growth reduction was concomitant with induced oxidative damage and decreased antioxidant defense system. To mitigate HHCB toxicity, a bioactive strain of diazotrophic plant growth-promoting Rhodospirillum sp. JY3 was isolated from heavy metal-contaminated soil in Jazan, Kingdom of Saudi Arabia, and applied to both crops. Overall, Rhodospirillum mitigated HHCB-induced stress by differently modulating the oxidative burst [malondialdehyde (MDA), hydrogen peroxide (H2O2), and protein oxidation] in both wheat and faba beans. This alleviation was coincident with improvement in plant biomass and photosynthetic efficiency, particularly in wheat crops. Considering the antioxidant defense system, JY3 augmented the antioxidants in both wheat and faba beans and the detoxification metabolism under HHCB stress conditions. More interestingly, inoculation with JY3 further enhanced the tolerance level of both wheat and faba beans against contamination with HHCB via quenching the lignin metabolism. Overall, this study advanced our understanding of the physiological and biochemical mechanisms underlying HHCB stress and mitigating its impact using Rhodospirillum sp. JY3, which may strikingly reduce the environmental risks on agriculture sustainability.